Tool-use experiments to determine the function of an incised ground stone artefact with potential symbolic significance. (2020) - Hayes, Elspeth; Spry, Caroline; Fullagar, Richard; Tuechler, Anna; Schell, Petra; Goulding, Megan
No abstract available